2015
DOI: 10.1016/j.seizure.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of TGFB, but not IL10, single nucleotide polymorphisms with febrile seizures

Abstract: Certain alleles, genotypes, and haplotypes in TGFB genes were over represented in patients with FS, which possibly could predispose individuals to this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…We have recently shown that there is a significant association between the presence of the +565A of IL-6, −590 C of IL-4, codon 10/CT (rs1982037) TGF-β and FS [25][26][27]. This study was performed to determine the associations between SNPs of TNF-α and FS in a group of Iranian patients.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that there is a significant association between the presence of the +565A of IL-6, −590 C of IL-4, codon 10/CT (rs1982037) TGF-β and FS [25][26][27]. This study was performed to determine the associations between SNPs of TNF-α and FS in a group of Iranian patients.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the haplotype frequencies of IL-10-592C/-819C/-1082A/-1352G were also decreased in patient group with FS, FS+, and GEFS+ compared to controls, although statistically insignificant (18.5% vs. 24.5%, P = 0.497). In contrast, Iranian FS study reported that IL-10-592, -819, and -1082 showed no significant allelic association [11].…”
Section: Discussionmentioning
confidence: 78%
“…Japanese FS study showed significant lower frequencies of the IL-10-592C/-819C/-1082A haplotype than controls [10]. In contrast, IL-10-592, -819, and -1082 showed no significant allelic association in Iranian FS study [11].…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, it may play a neuroprotective role in the case of prolonged convulsions, protecting nerve cells against ischaemic damage (3) . Interleukin 10 (IL-10) inhibits the production of proinflammatory cytokines, including TNF-α, IL-1, IL-6 and IL-8, and its increased levels observed in experimental studies after the onset of a seizure may indicate (20,23) . Literature data on the relationship between IL-10 and other cytokines (including IL-2, IL-4, IL-8, TNF-α) and FS are inconclusive (3,20) .…”
Section: Immune Factors -Cytokinesmentioning
confidence: 99%